Römisches Zaumzeug aus Pompeji, Herculaneum und Stabiae : Metallizäume, Trensen und Kandaren - Simon, Christina (Archaeologist), (Archaeopress Roman archaeology ;, 2014)
Few regions possess so many and mainly complete Roman bridles as do the Vesuvian sites. Singular find conditions permit both comprehensive antiquarian-historian analyses of their production, functionality, and everyday use and new approaches to their typology and chronology. The 103 catalogued specimens belong to four types of bronze headstalls, namely metallic noseband, bitless metal bridle ('hackamore'), multipartite metallic bridle ('metallic halter'), and muzzle as well as two types of bits, namely snaffle bit with circular cheekpieces and curb bit. All of them occurred in more or less numerous variants of local or provincial origin. Special attention is paid to the reconstruction of application methods and combinations of types as well as the replica of a snaffle bit with circular cheekpieces.